2001
DOI: 10.1007/s004680100102
|View full text |Cite
|
Sign up to set email alerts
|

The effect of elevated carbon dioxide and ozone on leaf- and branch-level photosynthesis and potential plant-level carbon gain in aspen

Abstract: Two aspen (Populus tremuloides Michx.) clones, differing in O 3 tolerance, were grown in a freeair CO 2 enrichment (FACE) facility near Rhinelander, Wisconsin, and exposed to ambient air, elevated CO 2 , elevated O 3 and elevated CO 2 +O 3 . Leaf instantaneous light-saturated photosynthesis (P S ) and leaf areas (A) were measured for all leaves of the current terminal, upper (current year) and the current-year increment of lower (1-year-old) lateral branches. An average, representative branch was chosen from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 55 publications
3
34
0
Order By: Relevance
“…Lombardozzi et al [19] reported that the typical coupling of stomatal conductance and photosynthesis does not always hold under high O 3 conditions, because O 3 can directly affect the function of stomatal cells so that g s no longer responds dynamically to changes in C i and the rate of carboxylation due to enzyme and membrane damage. Unchanged g s with increased C i in the second growing season, as observed in this study, indicated that the decrease in photosynthesis was independent of g s [15,36].…”
Section: Discussionsupporting
confidence: 78%
“…Lombardozzi et al [19] reported that the typical coupling of stomatal conductance and photosynthesis does not always hold under high O 3 conditions, because O 3 can directly affect the function of stomatal cells so that g s no longer responds dynamically to changes in C i and the rate of carboxylation due to enzyme and membrane damage. Unchanged g s with increased C i in the second growing season, as observed in this study, indicated that the decrease in photosynthesis was independent of g s [15,36].…”
Section: Discussionsupporting
confidence: 78%
“…In a FACE study on two aspen clones, CO 2 -enrichment to 560 p.p.m. increased the light-saturated photosynthetic rate of leaves by 34 and 26% (clones 216 and 259), whereas O 3 fumigation with about 1.5 times ambient decreased photosynthesis by 29 and 40% (Noormets et al 2001a). The +CO 2 + O 3 treatment increased photosynthesis by 15 and 19%.…”
Section: The Influence Of Elevated Co 2 + O 3 On Leaf Photosynthetic mentioning
confidence: 97%
“…Thus, the overall effect of elevated CO 2 and O 3 on growth was not as marked and was dependent on plant allometric responses, in contrast with the immediate response of leaf photosynthetic rate. Such responses may be species-and even clonedependent (Noormets et al 2001a). …”
Section: The Influence Of Elevated Co 2 + O 3 On Leaf Photosynthetic mentioning
confidence: 99%
“…The reduced net CO 2 assimilation in O 3 -exposed leaves is largely driven by a decrease in gross CO 2 assimilation rate by the Rubisco, but it also results from increased CO 2 losses through an enhanced respiration, as observed in poplar Noormets et al 2001;Reich 1983), Norway spruce (Küppers and Klumpp 1988), Scots pine (Kellomaki and Wang 1998;Skärby et al 1987), birch ) and beech (Kitao et al 2009). The increase in CO 2 efflux from respiration is supported by an enhanced glycolysis, pentose-phosphate pathway and TCA cycle activity (Dizengremel 2001).…”
Section: Carbon Assimilation and Leaf Senescencementioning
confidence: 99%